Pharmacokinetics and pharmacodynamics of the novel monobactam LYS228 in a neutropenic murine thigh model of infection. (15th October 2018) - Growcott, E J; Cariaga, T A; Morris, L; Zang, X; Lopez, S; Ansaldi, D A; Gold, J; Gamboa, L; Roth, T; Simmons, R L; Osborne, C S
Abstract: Objectives: The neutropenic murine thigh infection model and a dose-fractionation approach were used to determine the pharmacokinetic/pharmacodynamic (PK/PD) relationship of LYS228, a novel monobactam antibiotic with activity against Enterobacteriaceae including carbapenem-resistant strains. Methods: Mice ( n  =   4 per group) were inoculated with Enterobacteriaceae strains via intramuscular injection. Two hours post-bacterial inoculation, treatment with LYS228 was initiated. Animals were euthanized with CO2 24 h after the start of therapy and bacterial counts (log10 cfu) per thigh were determined. PK parameters were calculated using free ( f ) plasma drug levels. Results: Following a dose-fractionation study, non-linear regression analysis determined that the predominant PK/PD parameter associated with antibacterial efficacy of LYS228 was the percentage of the dosing interval that free drug concentrations remained above the MIC (% fT >MIC ). In a dose-dependent manner, LYS228 reduced the thigh bacterial burden in models established with Enterobacteriaceae producing β-lactamase enzymes of all classes (e.g. ESBLs, NDM-1, KPC, CMY-2 and OXA-48). The range of the calculated static dose was 86–649 mg/kg/day for the isolates tested, and the magnitude of the driver of efficacy was 37–83 % fT >MIC . % fT >MIC was confirmed as the parameter predominantly driving efficacy as evidenced by a strong coefficient of determination ( r 2   =   0.68). Neutrophils had minimal impact on the effect of LYS228 in the murine thigh infection model. Conclusions: LYS228 is efficacious in murine thigh infection models using β-lactamase-producing strains of Enterobacteriaceae, including those expressing metallo-β-lactamases, ESBLs and serine carbapenemases, with the PK/PD driver of efficacy identified as % T >MIC .